(untitled) (LIS TODAY, 2025)
The rapid growth of Information and Communication Technology (ICT) has changed how we live and work. In education, ICT has become essential, especially through e-learning. This study examines the role of e-learning in higher secondary education during the COVID-19 pandemic, focusing on teachers’ perceptions, experiences, and practices. A survey was conducted with 250 teachers, achieving an 86% response rate. Key findings highlight that 94.9% of respondents utilized e-learning platforms, primarily through Google Classroom and WhatsApp. While a substantial proportion of students participated in online classes, significant gaps in attendance were noted. Challenges such as slow internet speeds and difficulties in accessing information were prevalent. The findings underscore the need for improved infrastructure and training to enhance the effectiveness of e-learning.